Stable Border Bases for Ideals of Numerical Cartesian Sets (Communications in Mathematical Research, 2021)
In this paper, we discuss a special class of sets of bivariate empiricalpoints, namely, numerical cartesian sets. We find that the stable quotient bases fornumerical cartesian sets are unique if they exist. Furthermore, the correspondingborder bases are the unique stable border bases for the vanishing ideals of numericalcartesian sets.
Keywords: empirical point; numerical cartesian set; vanishing ideal; border base.